The overspent Singaporean : does financial literacy or self-control better explain over-indebtedness better? Evidence from highly indebted borrowers in Singapore - Tiong, Ting En (2016)
We analyse a sample of over-indebted individuals in Singapore to find out how financial literacy and self-control affects debt load. In this paper, we measured financial literacy using questions that test basic financial concepts as well as how respondents applied debt repayment strategies. Self-control was ascertained through the use of scales which captured innate self-control and spending preferences. We also studied how increased cognitive load created by an additional number of accounts affect self-control. Through our analysis, we found that having financial knowledge and applying rational debt repayment strategies do not necessarily reduce debt size amongst the overindebted. While our results show no significance for innate self-control, spending preferences and number of accounts were shown to increase debt size. This implies that policies targeted at financial education might not yield significant results in reducing debt loads, while policies focused on spending habits and limiting number of accounts might be more successful in helping the over-indebted overcome their financial circumstances.